Critical Dialogues about the Reading Process with In-service Teachers and Children - Koomi Kim; Maria Perpetua Liwanag; Violet Henderson; Peter Duckett (Networks: An Online Journal for Teacher Research, 2014)
This article investigates how teacher educators and teachers collaborate via dialogic interactions to support the development of elementary students’ reading strategies. By implementing comprehension-centered reading tools such as the Burke reading interview and strategy rulers in partnership with in-service teachers, we are able to sustain ongoing inquiry and evaluation of effective literacy practices that enhance student learning.